Wireless electrical stimulation at the nanoscale interface induces tumor vascular normalization - Changhao Li; Cairong Xiao; Lizhen Zhan; Zhekun Zhang; Jun Xing; Jinxia Zhai; Zhengnan Zhou; Guoxin Tan; Jinhua Piao; Yahong Zhou; Suijian Qi; Zhengao Wang; et al. (Bioactive Materials, 2022)
Pathological angiogenesis frequently occurs in tumor tissue, limiting the efficiency of chemotherapeutic drug delivery and accelerating tumor progression. However, traditional vascular normalization strategies are not fully effective and limited by the development of resistance. Herein, inspired by the intervention of endogenous bioelectricity in vessel formation, we propose a wireless electrical stimulation therapeutic strategy, capable of breaking bioelectric homeostasis within cells, to achieve tumor vascular normalization. Polarized barium titanate nanoparticles with high mechano-electrical conversion performance were developed, which could generate pulsed open-circuit voltage under low-intensity pulsed ultrasound. We demonstrated that wireless electrical stimulation significantly inhibited endothelial cell migration and differentiation in vitro. Interestingly, we found that the angiogenesis-related eNOS/NO pathway was inhibited, which could be attributed to the destruction of the intracellular calcium ion gradient by wireless electrical stimulation. In vivo tumor-bearing mouse model indicated that wireless electrical stimulation normalized tumor vasculature by optimizing vascular structure, enhancing blood perfusion, reducing vascular leakage, and restoring local oxygenation. Ultimately, the anti-tumor efficacy of combination treatment was 1.8 times that of the single chemotherapeutic drug doxorubicin group. This work provides a wireless electrical stimulation strategy based on the mechano-electrical conversion performance of piezoelectric nanoparticles, which is expected to achieve safe and effective clinical adjuvant treatment of malignant tumors.